A data analysis framework to predict the behaviour of macroeconomic indicators of countries. (8th September 2021) - Basariya, M.I. Nafeesathul; Punniyamoorthy, Murugesan
The impact of macroeconomic indicators on the economy of countries is difficult to establish correctly as the effects of these indicators are nonlinear and time variant. In this study, we have evolved new means to generate stationarity of such time series data. We have grouped the countries based on the mathematical model arrived during the stationarity test of economic indicators to analyse the pattern and magnitude of indicators that influences the economy and to suggest measures to follow the best economy in the group. The consumer price index and stock index data of countries like the USA, the UK, Brazil, India, Estonia and Latvia are considered for this purpose. The pattern of consumer price index and stock index of all the countries selected irrespective of their growth, was affected during the global financial crisis occurred during the year 2007 to 2009. The remedial measures to follow to reduce the gap are suggested.